2008
DOI: 10.1590/s1980-57642009dn20200006
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and activities of daily living inventories in the diagnosis of frontotemporal lobar degeneration and Alzheimer's disease

Abstract: The differential diagnosis between frontotemporal lobar degeneration (FTLD) and Alzheimer’s disease (AD) is often challenging.ObjectivesTo verify the usefulness of behavioral and activities of daily living inventories in the differential diagnosis between FTLD and AD.MethodsCaregivers of 12 patients with FTLD (nine with frontotemporal dementia, two with semantic dementia and one with progressive non-fluent aphasia) and of 12 patients with probable AD were interviewed. The Brazilian version of the Frontal Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Several instruments are available for assessing behavioral symptoms in patients with dementia including the Frontal Behavioral Inventory (FBI), which was devised specifically to assess the behavioral disturbance in FTLD. 32 - 34 Kertesz et al, 35 2000, administered the FBI in patients with FTD, PNFA, AD, vascular dementia and depressive disorder. They demonstrated that the scale correctly classified 92.7% of the FTD patients and demonstrated high internal consistency and inter-rater reliability.…”
Section: Discussionmentioning
confidence: 99%
“…Several instruments are available for assessing behavioral symptoms in patients with dementia including the Frontal Behavioral Inventory (FBI), which was devised specifically to assess the behavioral disturbance in FTLD. 32 - 34 Kertesz et al, 35 2000, administered the FBI in patients with FTD, PNFA, AD, vascular dementia and depressive disorder. They demonstrated that the scale correctly classified 92.7% of the FTD patients and demonstrated high internal consistency and inter-rater reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The Disability Assessment for Dementia was also adapted for Brazil 11 and seems to be useful for the characterization of functionality in frontotemporal dementia and AD, assessing both BADLs and IADLs as well as leisure activities, although these two groups do not show differences in functional performance. 12 The BADL index was developed by Sidney Katz in 1963 13 to study the results of treatment and prognosis among older and chronically ill people. The grades of the index summarize overall performance in bathing, dressing, going to the bathroom, transferring, continence, and feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho et al [ 13 ] found no significant difference in functional communication between AD and FTLD patients. Similarly, Bahia et al [ 14 ] found no significant differences between patients with AD and FTLD on DAD scores. In their sample, DAD did not prove accurate for differential diagnosis of these dementia types.…”
Section: Discussionmentioning
confidence: 94%